Safety margin after radiofrequency ablation of hepatocellular carcinoma: precise assessment with a three-dimensional reconstruction technique using CT imaging. (17th November 2018) - Jiang, Chunlin; Liu, Baoxian; Chen, Shuling; Peng, Zhenwei; Xie, Xiaoyan; Kuang, Ming
Abstract: Purpose: To analyse the precise ablative margin (AM) after radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC) and the correlation between AM and local tumour progression (LTP) with a three-dimension (3D) reconstruction technique. Methods: From March 2011 to May 2013, 134 patients who underwent RFA for 159 primary or recurrent HCCs within Milan criteria were enrolled. Contrast-enhanced computed tomography (CECT) scans were performed 1 week before and 1 month after treatment. The AM was measured in various directions using a 3D reconstruction technique that shows the index tumour and ablated zone on the same image. The average of all obtained AMs (average AM) and the smallest AM (min-AM) were calculated. Results: The min-AM after RFA ranged from 1 to 9.3 mm (median ± standard deviation, 4.8 ± 1.8 mm). LTP was observed in 19 tumours from 19 patients. The median min-AM was 3.1 ± 1.6 mm for patients with LTP, while the median min-AM of patients without LTP was 5.1 ± 1.8 mm ( p  = 0.023). After RFA, the 1-, 2- and 3-year LTP rates were 10.9, 25.9 and 35.1%, respectively, for patients with min-AM <5 mm, and 4.1, 4.1 and 4.1%, respectively, for patients with min-AM ≥5 mm ( p  = 0.016). Multivariate analysis showed that only min-AM <5 mm was an independent risk factor for LTP after RFA ( p  = 0.044, hazard ratio =4.587, 95% confidence interval, 1.045–22.296). Conclusions: The 3D reconstruction technique is a precise method for evaluating the post-ablation margin. Patients with min-AM less than 5 mm had a higher probability of developing LTP.